تأثير تمرينات المقاومة الباليستية في تطوير بعض القدرات البدنية وانجاز 25م لسباحي حرة البحث مستل من رسالة الماجستير - فتاح, نةبةز عبدالله; الله, أحمد جمال فتح (Sulaimani Journal for Humanities, 2022)
The current research discusses the ballistic resistance exercises and their impact on the development of physical capacity and the completion of 25 m freestyle swimming. The importance of research lies in studying the effect of ballistic resistance exercises in the development of some physical capacity of swimmers and the completion of 25 m freestyle swimming to find new and modern ways to develop the physical capabilities of short distance swimming Research Aims: The differences between the cardiac and dimensional measurements of the control group in the effect of ballistic resistance exercises on the development of some physical and kinesthetic abilities and technical performance and completion of the 25m freestyle swimmer. The differences between the cardiac and dimensional measurements of the experimental group in the effect of ballistic resistance exercises on the development of some physical and kinesthetic abilities and technical performance and completion of the 25m freestyle swimmer. The differences between the two cardiac and dimensional measurements of the control and experimental group on the development of some physical and kinesthetic abilities and technical performance and completion of the 25m freestyle swimmer. The researcher used the experimental method to tackle the research questions. To answer the research questions, the sample was selected from the junior category, which were seven players, three players were randomly selected to represent the control group and three other players to represent the experimental group. One player was excluded. The percentage of the research sample is (35,29%) from the original sample. In the current research, the research sample was divided into two equal groups, the first group was subjected to the traditional training method (the control) and the second group was given the training method using the ballistic resistance method (experimental). Equivalence was made in the required research variables, both groups (control and experimental) were tested on the same day. In addition, the following tests used to measure ballistic resistance and physical abilities: vertical jump from stability, wide jump from stability, arms frequency 25 m freestyle, push-up for 10 seconds, 25 m freestyle achievement, medical ball throwing. The current research is, on one hand, a strong motivation for the researcher to do more research in order to encourage researchers to develop and find new techniques, one the other hand, the research finding and procedures are achieved in the research to help coaches who face difficult circumstances in preparing the swimmers. The most important inference The ballistic exercises that were applied to the participants of the experimental group had an effect on improving the collection of physical and motor abilities of the participants. Significant contradiction appeared between the control group and the experimental group in the post test in the technical performance tests and the achievement of (25) m free style of swimming, and the difference was in favor of the post test for the experimental group. The most important recommendation The use of ballistic resistance exercises when freestyle swimming players are trained because it has a role in improving the results of the highest strength in the shortest time. The results of the current study are disseminated to swimming coaches to benefit from them and to take into consideration the results of this study by the coaches when preparing their training program